Seasonal changes in beach resilience along an urbanized barrier island - Mendoza, Ernesto Tonatiuh; Torres-Freyermuth, Alec; Ojeda, Elena; Medellín, Gabriela; Rioja-Nieto, Rodolfo; Salles, Paulo; Turki, Imen (Frontiers in Marine Science, 2022)
Beach width, dune height, and vegetation coverage are key parameters to assess beach resistance and resilience to storms. However, coastal development often causes beach ecosystem degradation due to poor coastal management. We propose a Coastal Resilience Index from Remote Sensors (CRIfRS) for urbanized coasts based on aerial photogrammetry. The study area, located along a 7.8 km stretch of coast on a barrier island, is characterized by persistent alongshore sediment transport and the presence of coastal structures and beach-front houses. Contrary to previous studies, we focus on anthropogenic perturbations (coastal urbanization and coastal structures), instead of hydrodynamic conditions (storms), since erosion in this region is mainly associated with alongshore sediment transport gradients induced by coastal structures. Thus, the CRIfRS is based on the relation of three indicators that affect the beach functionality for coastal protection: beach width, coastal structure influence area, and vegetation coverage. The CRIfRS was divided into five categories: Very Low resilience (VL), Low resilience (L), Medium resilience (M), High resilience (H), and Very High resilience (VH). The CRIfRS presented an important spatial and temporal variability due to changing environmental conditions and the deployment of new coastal structures. For the study period, the percentage of the coast within the VL and L resilience classification increased, whereas the percentage of the coast classified as M, H, and VH resilience decreased. During the winter storm season, the resilience increased mainly due to the cross-shore transport whilst during mean wave conditions (i.e., sea-breeze conditions) the long-shore transport becomes more persistent and thus the coastal structures play an important role interrupting the sediment flux. Additionally, the CRIfRS trajectory shows an overall increase of the L resilience and an overall decrease of the H resilience values. This study highlights the important role of anthropogenic perturbations on the assessment of coastal resilience for highly urbanized coasts. The CRIfRS can help to improve the coastal management by assessing the coastal protection capability of beaches considering both natural and anthropogenic factors.